PENGARUH AKTIPITAS SEKTOR-SEKTOR PEREKONOMIAN TERHADAP KUALITAS LINGKUNGAN KITA: PENERAPAN ANALISIS INPUT-OUTPUT HIBRID DAN METODA INDORANI - Faried Wijaya Mansoer (Journal of Indonesian Economy and Business (JIEB), 2000)
Sustainable development has been widely accepted as a general policy concept. Development process, as an overall production activites, produces various negative waste on environment. Policies and efforts should be implemented in order to eliminate them. Measuring the impact will be the beginning step. This paper is based upon an extention version of a research sponsored by The Directorate General of Higher Education, by applying hibrid input-output analysis and Indorani method to quantify such impacts. Its target, field, and impact dimension are wider and mutually strengthening such that conclusion and policy could be drawn and formulated more focused.